Stochastic Stability of Short-Run Market Equilibrium Under Variations in Supply - Turnovsky, Stephen J. (Quarterly Journal of Economics, 1968)
I. Introduction, 666. — II. Expectations and deterministic stability, 668. — III. Stochastic stability, 672. — IV. Stochastic stability of simple first order system, 675. — V. Stochastic stability of short-run fluctuations, 676. — VI. Stochastic stability with autocorrelated disturbances, 680. — VII. Concluding remarks, 681.